Quantification of the coupling relationship between ecological compensation and ecosystem services in the Yangtze River Economic Belt, China. (March 2022) - Jiang, Yanan; Guan, Dongjie; He, Xiujuan; Yin, Boling; Zhou, Lilei; Sun, Lingli; Huang, Danan; Li, Zihui; Zhang, Yanjun
Abstract: With the rapid development of human society, the self-regulation ability of ecosystem services has lagged far behind the degree of human destruction. As an effective environmental incentive policy, ecological compensation plays an important role in improving the ecology of all regions in the world. This study discussed the willingness of farmers to participate in ecological compensation in the Yangtze River Economic Belt based on the results of a questionnaire, analyzed the influencing factors, established differential ecological compensation standards, and explained the coupling relationship between ecological compensation and ecosystem services. First, the contingent valuation method (CVM) was used to analyze the ratio of farmers' willingness to accept and willingness to pay and to identify the factors affecting farmers' willingness to accept ecological compensation. The minimum-data approach was used to establish different types of ecological compensation standards in various administrative regions of the Yangtze River Economic Belt. Finally, the efficient guidelines for ecological compensation standards were analyzed. The results showed that the expected value ratio of farmers' willingness to accept and willingness to pay in the Yangtze River Economic Belt was 9.26 times, the actual compensation standard was generally lower than the theoretical compensation standard, and the degree of participation in seven administrative regions was less than 10%. When the compensation standard reached a certain threshold, the supply of ecosystem services would exceed the needs of regional development, leading to a "marginal effect", so compensation standard should be no longer increased. The results of this study provide scientific advice for formulating compensation standards, perfecting the ecological compensation mechanism, and improving the efficiency of ecological compensation in the rapidly developing regions represented by the Yangtze River Economic Belt. Highlights: Farmers' willingness to accept is 9.26 times of willingness to pay. The per capita annual income is the most important factor affecting farmers' willingness to pay. The minimum data model was used to establish different types of ecological compensation standards. Ecological compensation and ecosystem services has coupling relationship and marginal effects.